Factors Affecting the Integrity of Financial Statements: Before and During the Pandemic - Asfeni Nurullah; Tertiarto Wahyudi; Asfeni Nurullah (Jurnal Ekonomi dan Bisnis Jagaditha, 2022)
This study aims to determine the effect of auditor switching, audit tenure, and financial distress on the integrity of financial statements before and during the pandemic. The subject of this study is the financial sector which is listed on the Indonesia Stock Exchange in 2019 and 2020. The method used in this study is a quantitative method. The population used in this study were companies in the financial sector for the period 2019 and 2020. The sample of the study was taken using a purposive sampling technique so that there were 106 samples. The study data analysis technique used the Statistical Program for Social Software (SPSS) version 24.0 with descriptive statistics and multiple linear regression. The integrity of the financial statements in this study is measured using conservatism. The results of the study partially show that auditor switching and audit tenure have no significant effect on the integrity of financial statements before the pandemic and during the pandemic, while financial distress has no effect on report integrity before the pandemic but has a significant negative effect on the integrity of financial statements at the time of the pandemic. During the pandemic, there was a significant difference between the integrity of financial statements before and during the COVID-19 pandemic.